COMPETITIVE ADVANTAGES OF E-COMMERCE: TRUST IN E-COMMERCE, SERVICE QUALITY, ONLINE PROMOTION, AND APPLICATION CONVENIENCE ON SHOPPING DECISIONS - Etvin R. Tamher; Aisah Asnawi; Merry Margareth Pelupessy (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to analyze the impact of brand trust, service quality, online promotion, and application ease of use on purchasing decisions in the e-commerce sector. The study uses a descriptive research type with a quantitative approach, involving 115 respondents from Ambon City who have shopped on different e-commerce platforms more than twice. The sampling technique applied is purposive sampling, and the data were analyzed using Partial Least Square (PLS). The results show that all variables—brand trust, service quality, online promotion, and application ease of use—positively and significantly influence purchasing decisions. Among these, service quality has the strongest effect, indicating that factors such as responsiveness, delivery assurance, and seller empathy are crucial in consumer decisions to purchase online. Brand trust, online promotion, and ease of use also play significant roles, supporting consumer confidence and enhancing the shopping experience. The findings suggest that e-commerce platforms should prioritize improving service quality while maintaining strong brand trust, effective promotions, and user-friendly applications to increase consumer purchasing decisions. This study contributes to a deeper understanding of consumer behavior in the e-commerce industry and offers practical implications for improving e-commerce platforms to meet consumer needs.